Electrochemical properties of graphitic carbon nitrides. (1st January 2014) - Jorge, A. Belen; Corà, F.; Sella, A.; McMillan, P.F.; Brett, Daniel J.L.
Lithium-ion batteries (LIBs) are the current devices of choice for portable energy storage applications; however, improvements in energy and power densities are required to sustain future more demanding tasks, such as those associated with automotive transport. Commercially, LIB anodes are typically made from graphitic carbon-based systems that present bottlenecks associated with surface passivation and slow intercalation kinetics. We have investigated layered/graphitic carbon nitrides (gCNMs) as alternative anode materials; their unique structure and chemistry enable new intercalation processes not available for pure-C graphite. Our gCNMs are prepared from C, N-containing precursors treated at different temperatures. Cyclic voltammetry showed clear oxidation/reduction cycles in the 0.5–1.5 V range indicating that Li + intercalation took place resulting in electric conduction properties of the previously semiconducting material. Higher reaction temperatures lead to buckling of the graphitic layers and consequent loss of planarity, with a negative effect on their electrochemical performance.